2006
DOI: 10.1007/s00417-005-0167-4
|View full text |Cite
|
Sign up to set email alerts
|

TFF peptides and mucins are major components of dacryoliths

Abstract: Dacryoliths consist partly of secreted mucins comparable with the mucin spectrum of the epithelium of healthy nasolacrimal ducts. Beside TFF1 and TFF3, both of which are produced under healthy circumstances, TFF2 is additionally induced and secreted in cases of dacryolithiasis. All three TFF peptides appear to be augmented in dacryoliths. With regard to their rheologic properties, TFF peptides may play a functional role in dacryolith formation. However, our results raise the question of whether TFF peptides pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
(44 reference statements)
3
30
0
10
Order By: Relevance
“…TFF2 is also ectopically secreted from a variety of mucous epithelia during stone diseases, such as nephrolithiasis, hepatolithiasis, dacryolithiasis, and cholecystolithiasis (135,136). Thus, TFF2, together with MUC6, would be a prime candidate for initiating the complex process of stone formation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…TFF2 is also ectopically secreted from a variety of mucous epithelia during stone diseases, such as nephrolithiasis, hepatolithiasis, dacryolithiasis, and cholecystolithiasis (135,136). Thus, TFF2, together with MUC6, would be a prime candidate for initiating the complex process of stone formation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This suggests bacterial infection is one of the processes involved in the creation of dacryoliths. In addition, proteomic analysis revealed that the TFF peptide, considered as the predominant component in previous report [3] , was not a major component of the dacryoliths in our study. However, the possibility of the TFF peptide may not be excluded because no histological examination was performed in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Paulsen et al [3] reported that trefoil factor (TFF) peptide and mucins are the major components of dacryoliths. Iliadelis et al [4] performed a histochemical analysis of dacryoliths in a series of DCR procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Mucins and TFF peptides are structural components of precipitation extracted from the lacrimal passages. It has not yet been verified whether the presence of those substances is caused by their participation in precipitation forming initiative process or is a response to the existing pathological process [33]. …”
Section: Functional Anatomy Of the Lacrimal Pathwaysmentioning
confidence: 99%